The human right to water : a legal comparative perspective at the international, regional and domestic level / Jimena Murillo Chávarro. - Murillo Chávarro, Jimena (Intersentia, 2015)
This book summarises the history of the human right to water and examines its main content and the obligations that derive from this right. The main purpose of the recognition of the human right to water is to guarantee to everyone access to sufficient, safe and affordable drinking water to satisfy personal and domestic uses. This book discusses whether the human right to water is recognised as a derivative right or as an independent right at three levels - at universal, regional and domestic - where human rights are recognised and enforced. At the domestic level a case study approach has been used with focus on Argentina, Bolivia, Chile and Colombia.Freshwater resources are not static; they are constantly flowing and crossing international boundaries. This situation and the relative scarcity of water resources have a direct impact on a state's capacity to realise the human right to water. The human right to water is examined in a transboundary water context, where the use and management of an international watercourse in one riparian state can directly or indirectly affect the human right to water in another riparian state. For this reason, this book analyses whether the core principles of international water law can be used to contribute to the realisation of the extraterritorial application of the right to water.